Analisis Stok Barang Menggunakan Algoritma K-Nearest Neighbor Dan Naïve Bayes Untuk Meningkatkan Efisiensi Persediaan Barang Retail Pada PT. XXX - Restu Putra, Catur; Anggai, Sajarwo; Susanto, Agung Budi (Universitas Pamulang, 2026)
Efficient inventory management is a strategic necessity for retail industries that operate under highly fluctuating demand conditions. PT XXX continues to experience inaccuracies in determining stock requirements because the analysis is still carried out manually using a three-month average sales calculation. This approach is unable to capture actual warehouse variations, resulting in frequent overstock and understock conditions. This study develops a machine learning–based stock classification model using the K-Nearest Neighbor (K-NN) and Naïve Bayes algorithms by utilizing key operational warehouse variables, including average sales, ending stock, and Days of Inventory (DOI). The dataset consists of 4,324 records from November 2024 to October 2025 and was processed using Orange Data Mining. Performance evaluation was conducted using accuracy, precision, recall, and confusion matrix. The results show that K-NN achieved the best performance, with 96.80% accuracy in the prediction model and 93.00% in the test & score evaluation, outperforming Naïve Bayes, which achieved approximately 90%. The study also produced a two-level classification mapping stock status (High/Low) and warehouse recommendations (Low/Enough/Excess) which revealed a significant imbalance between High and Low categories. These findings demonstrate that machine learning–based classification methods can enhance stock assessment accuracy and support more adaptive and efficient restocking decisions in retail inventory management